The competitive tier model – Element subtraction in German and Pomeranian - Gertjan Postma (Glossa, 2019)
Competition of segmental material is inherent to all proposals of phonological template satisfaction. Segments are aligned with a prosodic template and compete for prosodic space. This vowel competition for space is well-known from the Semitic languages. In this paper, we argue that competition is also present in West-Germanic languages, albeit in disguised form. Basing ourselves on new Pomeranian data, we propose a competitive vocalic tier on which elements compete for prosodic slots besides the well-known vocalic tier that allows for element coalescence. An axiomatic model is developed that predicts alternations such as the [ɑi]-[ɪ] and [e]-[ɪ] root alternation (German treten – tritt ‘(he) step(s), Pomeranian gaita-git ‘(he) pour(s)’). The model allows us to solve three riddles in German morphology: 1. the “epenthesis conundrum”, i.e. the anti-correlation between OCP-driven schwa epenthesis between root and suffix in German (rett[ə]t/*rett versus *rät[ə]t/rät) and root alternations in present tense verbs (alternating verbs): retten – er rettet, raten – (er) rät (Neef 1997; Trommer 2010; Scheer 2016); 2. the “imperative conundrum” (Raffelsiefen 2016), which describes a correlation within the class of alternating verbs: the correlation between |A|-subtraction in a subset of alternating verbs (geben – gibt ‘give(s)’) and ending-less imperatives in German (gib! ‘give!’); 3. the vowel shortening conundrum: change in quantity of the root vowel in function of the type of vowel alternation: [e:]-[i] versus [a:]-[ɛ:]. A formal model is presented that provides us with a calculus of coalescence and competition of phonological features.Languages: Standard German; Pomeranian; Dutch; Low Saxon; Limburgian; Frisian.